Looking for a «Patriot King» Scholar of the «Science of Politics»: The English Translation of Jacques-Joseph Duguet’s Institution d’un Prince in the Walpole Era - Della Fontana, Aris (Diciottesimo Secolo, 2025)
This article analyses the English translation of Jacques-Joseph Duguet’s Institution d’un Prince (1739). The Institution of a Prince, published in 1740 by Robert Dodsley, was the result of an editorial project orchestrated by the Patriot Opposition with two main objectives. First, to use the contents of the Institution to criticise the Walpole government by exposing the political, economic and moral shortcomings that were leading Great Britain into decline. Second, to use the work as a tool to educate Frederick, Prince of Wales, ensuring that – unlike his father, George II – he would become a true «patriot king». This article also underscores that those who imported Duguet’s text were careful to emphasise that the Jansenist abbot advocated an absolutist model of «pure» and «irresistible» monarchy – an aspect at odds with the Glorious Revolution’s principles of limiting royal prerogative and sharing power between the king and Parliament. By addressing this apparent paradox, this case study contributes to the scholarship on the active role played by recipient entities in cultural transfers, implying that interpretation can be highly flexible and creative. Indeed, the English disseminators of the Institution d’un Prince did not treat the text with reverential awe; rather, through the use of a hugely significant paratext and a ‘creative’ translation, they critiqued and selected Duguet’s heterodox content to serve a political and intellectual agenda of which he himself would never have approved.